Strategi Peningkatan Daya Saing Ikan Bandeng Olahan Di Kota Serang Banten - Ridloudin, Ahmad; Raharja, Sapta; Suryahadi, - (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2019)
Milkfish is a fish belonging to the Chanidae tribe which is spread throughout most parts of Indonesia. The method used in determining respondents is purposive sampling method. Based on the results of the SWOT analysis, there are four strategies were obtained in increasing the competitiveness of processed milkfish include; (a) developing a sustainable milkfish agribusiness system and business, (b) building a business system that is competitive, synergistic, mutually beneficial and technology focused on efficiency, (c) institutional, partnership and integrated development of integrated processed fish SMEs, and (d) government involvement in policies in the form of regulations which favor the improvement of milkfish processed SME s in Serang City.The result QSPM analysis found that the alternative strategy which becomes the main priority to increased competitiveness of processed milkfish in Serang City is building a competitive business system, synergy, mutual benefit and technology focus for eficiency